Review of Routes to Administer Medication During Prolonged Neonatal Resuscitation. Issue 4 (April 2018) - Wagner, Michael; Olischar, Monika; O'Reilly, Megan; Goeral, Katharina; Berger, Angelika; Cheung, Po-Yin; Schmölzer, Georg M.
Abstract : Objective: During neonatal cardiopulmonary resuscitation, early establishment of vascular access is crucial. We aimed to review current evidence regarding different routes for the administration of medications during neonatal resuscitation. Data Sources: We reviewed PubMed, EMBASE, and Google Scholar using MeSH terms "catheterization, " "umbilical cord, " "delivery room, " "catecholamine, " "resuscitation, " "simulation, " "newborn, " "infant, " "intraosseous, " "umbilical vein catheter, " "access, " "intubation, " and "endotracheal." Study Selection: Articles in all languages were included. Initially, we aimed to identify only neonatal studies and limited the search to randomized controlled trials. Data Extraction: Due to a lack of available studies, studies in children and adults, as well as animal studies and also nonrandomized studies were included. Data Synthesis: No randomized controlled trials comparing intraosseous access versus peripheral intravascular access versus umbilical venous catheter versus endotracheal tube versus laryngeal mask airway or any combination of these during neonatal resuscitation in the delivery room were identified. Endotracheal tube: endotracheal tube epinephrine administration should be limited to situations were no vascular access can be established. Laryngeal mask airway: animal studies suggest that a higher dose of epinephrine for endotracheal tube and laryngeal mask airway is required compared with IV administration, potentially increasing side effects. Umbilical venous catheter: European resuscitation guidelines propose the placement of a centrally positioned umbilical venous catheter during neonatal cardiopulmonary resuscitation; intraosseous access: case series reported successful and quick intraosseous access placement in newborn infants. Peripheral intravascular access: median time for peripheral intravascular access insertion was 4–5 minutes in previous studies. Conclusions: Based on animal studies, endotracheal tube administration of medications requires a higher dose than that by peripheral intravascular access or umbilical venous catheter. Epinephrine via laryngeal mask airway is feasible as a noninvasive alternative approach for drug delivery. Intraosseous access should be considered in situations with difficulty in establishing other access. Randomized controlled clinical trials in neonates are required to compare all access possibilities described above.